Effective Arabic Language Learning Programme Management Model At The Pekanbaru Islamic Boarding School - Alfan Zuhdi; Hakmi Wahyudi; Muhammad Auli Rahman (Universitas Islam Negeri Palopo, 2026)
Arabic language learning in Islamic boarding schools plays a strategic role in supporting the understanding of Islamic sources and the development of students' academic and communicative competencies. One of the determining factors for the success of this learning is the effectiveness of learning programme management integrated with the application of bi'ah 'arabiyah. This study aims to analyse the patterns of Arabic language learning programme management based on bi'ah 'arabiyah and its contribution to the effectiveness of learning at the Abu Darda Islamic Boarding School in Pekanbaru and Darul Hadis Al-Watsar. This study uses a descriptive qualitative approach with data collection techniques in the form of participatory observation, in-depth interviews, and documentation. The research informants included the boarding school leaders, the head of the language department (qism al-lughah), and Arabic teachers selected through purposive sampling. The results showed that the Arabic language learning programme management pattern was implemented systematically through four management functions, namely planning, organising, implementing, and supervising. The application of bi'ah 'arabiyah has been proven to contribute positively to improving the language skills of students, although there are still obstacles such as limited vocabulary and psychological factors of beginner students. Overall, this study concludes that planned and sustainable management of Arabic language learning programmes based on bi'ah 'arabiyah can improve the effectiveness of Arabic language learning in Islamic boarding schools.